Estudo da substituição parcial de areia natural por areia descartada de fundição para produção de concreto convencional - Cremonez, Claiton (2022)
The construction industry is a major generator of polluting materials. Simple construction or demolition processes provide substantial amounts of waste. There is also the fact that to produce raw material for this sector there is a great environmental impact. Deposits for the extraction of aggregates and binders, for example, occupy large areas and often cause significant environmental damage. In parallel, the metal casting industries produce several million tons of by-products worldwide. In Brazil alone, about 3 million tons of sand discarded from foundry are produced annually. Waste foundry sand (WFS) is the main residue of the metal casting industry. Currently this material has as main destination disposal disposal landfills. However, the disposal of waste foundry sand (WFS) to landfills is becoming a problem due to the high cost of transportation and disposal. To use WFS on a large scale, research is being conducted to enable its use in the concrete manufacturing industry as a partial replacement of fine aggregate. This research was carried out in order to evaluate the mechanical strength properties of concrete, in which natural sand was partially replaced by (WFS). Natural sand was replaced with five percentages (0%, 20%, 40%, 60% 80% and 100%) of mass WFS, in addition to a reference trace. The study involved the molding of 936 specimens 10x20 cm and used traces of a concrete mill in the metropolitan region of Curitiba – PR. Water/Cement 0.40 0.50 0.60 and 0.70 were addressed in the study. The compression strength assays were performed at the ages of 7, 28, 63, 91 and 365 days. In addition to the mechanical strength tests, density tests were also performed in the fresh and hardened state and determination of water absorption by capillarity according to NBR9779:2012. Due to the large number of samples it was possible to elaborate studies involving standard deviation and coefficient of variation. These data obtained in the study pointed to a great reliability of the results.